(untitled) (Konferensiyalar | Conferences, 2024)
The revival of the cultural potential of each people and its disclosure through the education system, the inclusion of social and pedagogical processes into the content of the education of ethnic culture are the most important tasks of modern society. The global challenge of civilizational development is the creation of a single multicultural and educational space based on a multilateral dialogue of cultures that promotes the mental compatibility of people in the context of their complementarity and mutual enrichment. Based on the ethnoculturological approach, the essential characteristics and basic structural components of the ethnocultural education system are determined, and personal, ethnopedagogic, linguistic, bilinguistic and moral aspects of the education system are revealed. From the point of view of procedural and efficient approach the essence of ethnocultural education system is interpreted as a process and a result of socio-historical development of ethnos, its main trends and features, and the readiness for ethnic self-identification is interpreted as a core quality in the structure of ethnic culture. It is alleged that the study of the ethnocultural environment in the system of formation and the pedagogical foundations of its formation should contribute to the realization of the cultural core of the content of education on the basis of universal human and regional values.